High-tensile steel plate

JP2026143013APending Publication Date: 2026-09-08NIPPON STEEL CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025030359
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2026-09-08

AI Technical Summary

Benefits of technology

【0012】 本発明に係る上記態様によれば、優れた耐摩耗性と低温靭性を有する非調質の高張力鋼板を提供することができる。特に、上記態様の高張力鋼板は、焼戻し等の熱処理を省略した上で、優れた耐摩耗性と低温靭性を実現できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026143013000001
    Figure 2026143013000001
  • Figure 2026143013000002
    Figure 2026143013000002
  • Figure 2026143013000003
    Figure 2026143013000003
Patent Text Reader

Abstract

To provide a non-heat-treated, high-tensile steel sheet with excellent wear resistance and low-temperature toughness. [Solution] A high-tensile steel sheet having a chemical composition in mass%, containing C: 0.110% or more and 0.210% or less, Si: 0.10% or more and 0.40% or less, Mn: 1.00% or more and 2.20% or less, P: 0.020% or less, S: 0.0060% or less, Al: 0.010% or more and 0.050% or less, Ti: 0.010% or more and 0.020% or less, N: 0.0010% or more and 0.0060% or less, B: 0.0005% or more and 0.0020% or less, and O: 0.004% or less, with the remainder being Fe and impurities, and having 5,000 or fewer cementite particles with a major axis of 400 nm or more contained in a 100 μm × 100 μm square area.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to high-tensile steel sheets. [Background technology]

[0002] High-tensile steel sheets are used in components of industrial machinery and transport equipment, and in some cases, high wear resistance is also required. Furthermore, high-tensile steel sheets are often required to have low-temperature toughness, considering harsh operating environments.

[0003] Generally, high-tensile steel sheets are hardened to achieve high strength, and their microstructure is often transformed into high-strength structures such as martensitic or bainite structures that undergo low-temperature transformations. However, generally, steel in the as-hardened state has poor low-temperature toughness.

[0004] Tempering is often performed as a method to improve the low-temperature toughness of high-tensile steel sheets. For example, Patent Document 1 describes how tempering a bainite and martensite-based structure at a temperature of 650°C or lower ensures excellent low-temperature toughness, with an absorbed energy of 100 J or more in a 2 mm V-notch Charpy impact test at -60°C.

[0005] Furthermore, a method of controlling the cooling pattern is known as a way to improve the low-temperature toughness of high-tensile steel sheets without tempering. For example, Patent Document 2 discloses that by controlling the bainite transformation temperature, the ductile-brittle transition temperature (vTrs) in the 2mm V-notch Charpy impact test can be lowered relative to the yield strength, thereby improving the strength-toughness balance. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] Patent No. 6582590 [Patent Document 2] Patent No. 6006477 [Overview of the project] [Problems that the invention aims to solve]

[0007] In this case, while the tempering method disclosed in Patent Document 1 can exhibit excellent low-temperature toughness, no consideration has been given to wear resistance. As mentioned above, tempering can improve low-temperature toughness, but it also reduces strength. Generally, wear resistance depends on strength, so if low-temperature toughness is ensured through tempering, wear resistance may decrease. Therefore, it has been difficult to achieve both wear resistance and low-temperature toughness in high-tensile steel sheets. Furthermore, if tempering is performed, productivity decreases, so it is preferable to omit it.

[0008] Furthermore, Patent Document 2 omits tempering and improves the balance between strength and low-temperature toughness. However, in the case of Patent Document 2, no consideration was given to wear resistance. In this case, only the same level of wear resistance as when strength is reduced by tempering can be obtained.

[0009] This invention was made in view of these circumstances, and aims to provide a high-tensile steel sheet having excellent wear resistance and low-temperature toughness. [Means for solving the problem]

[0010] This invention is based on the above findings, and its gist is as follows.

[0011] (1) A high-tensile steel sheet according to one aspect of the present invention has a chemical composition in mass% of: C: 0.110% or more, 0.210% or less Si: 0.10% or more, 0.40% or less, Mn: 1.00% or more, 2.20% or less, P: 0.020% or less, S: 0.0060% or less, Al: 0.010% or more, 0.050% or less, Ti: 0.010% or more, 0.020% or less, N: 0.0010% or more, 0.0060% or less, B: 0.0005% or more and 0.0020% or less, and O: 0.004% or less , with the balance being Fe and impurities, the number of cementite particles having a major axis of 400 nm or more contained in a 100 μm × 100 μm square region is 5,000 or less. (2) The high-strength steel sheet according to (1) above, wherein the chemical composition, in mass%, Nb: 0.030% or less, Cu: 0.50% or less, Ni: 0.50% or less, Cr: 0.50% or less, Mo: 0.50% or less, V: 0.10% or less, Mg: 0.0050% or less, Ca: 0.0050% or less, and REM: 0.0200% or less, may contain one or more selected from the group consisting of (3) The high-strength steel sheet according to (1) or (2) above, wherein the chemical composition, in mass%, W: 0.100% or less, Co: 0.100% or less, Zr: 0.050% or less, Hf: 0.020% or less, Te: 0.050% or less, As: 0.050% or less, Sr: 0.020% or less, Sn: 0.100% or less, Sb: 0.050% or less, Bi: 0.100% or less, Ta: 0.100% or less, Zn: 0.020% or less, Pb: 0.090% or less, and Se: 0.020% or less, may contain one or more selected from the group consisting of (4) In the case of the high-tensile steel plate described in (1) or (2) above, the weight loss rate when a gouging abrasion test is performed under the conditions of a rotational speed of 30 rpm, a load of 14.1 kgf, and an ambient temperature of 200°C may be 0.12 g / min or less. (5) In the case of the high-tensile steel plate described in (3) above, the weight loss rate when a gouging abrasion test is performed under the conditions of a rotational speed of 30 rpm, a load of 14.1 kgf, and an ambient temperature of 200°C may be 0.12 g / min or less. [Effects of the Invention]

[0012] According to the above embodiment of the present invention, it is possible to provide a non-heat-treated high-tensile steel sheet having excellent wear resistance and low-temperature toughness. In particular, the high-tensile steel sheet of the above embodiment can achieve excellent wear resistance and low-temperature toughness without heat treatment such as tempering. [Modes for carrying out the invention]

[0013] The following describes a non-heat-treated high-tensile steel sheet according to one embodiment of the present invention. However, the present invention is not limited to the configuration disclosed in this embodiment, and various modifications are possible without departing from the spirit of the invention. Furthermore, the numerical limit ranges described below, separated by "~", include both a lower limit and an upper limit. Numerical values ​​indicated as "less than" or "greater than" are not included in the numerical range.

[0014] <1. Results of the inventors' investigation> First, the inventors investigated a method to improve the wear resistance of high-tensile steel sheets regardless of their strength. As a result, they found that even with equivalent strength, the wear resistance of high-tensile steel sheets can be improved by reducing the number of coarse cementite particles, which are the starting points for the generation of microcracks during wear. Furthermore, they found that reducing the number of coarse cementite particles in high-tensile steel sheets suppresses the occurrence of brittle fracture at low temperatures and improves low-temperature toughness.

[0015] Next, the inventors investigated the precipitation behavior of coarse cementite and methods for reducing it. As a result, they found that coarse cementite mainly precipitates from the bainite lath interface during bainite transformation while cooling. Furthermore, they found that by introducing a large amount of dislocations into the austenite during hot rolling before cooling, the precipitation of fine cementite from inside the bainite lath is promoted, thereby reducing the precipitation of coarse cementite from the bainite lath interface.

[0016] Based on the above findings, the requirements of one embodiment of the present invention are described in detail below.

[0017] <2. High tensile strength steel plate> The chemical composition of the high-tensile steel sheet according to this embodiment will be described below. In the following description of the chemical composition, "%" in the content means "mass%".

[0018] (C: 0.110% or more, 0.210% or less) Carbon (C) is an element that increases the strength and improves the wear resistance of steel. From the viewpoint of ensuring strength and wear resistance, in this embodiment, the carbon content is 0.110% or more. Preferably, the carbon content is 0.130% or more. On the other hand, if the carbon content exceeds 0.210%, the hardness becomes excessively high, and the low-temperature toughness deteriorates. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the carbon content is 0.210% or less. Preferably, the carbon content is 0.200% or less.

[0019] (Si: 0.10% or more, 0.40% or less) Si is a deoxidizing element. From the viewpoint of ensuring the deoxidizing effect, the Si content in this embodiment is 0.10% or more. On the other hand, if the Si content exceeds 0.40%, the wear resistance and low-temperature toughness decrease due to the increase in island-like martensite. From the viewpoint of ensuring wear resistance and low-temperature toughness, the Si content in this embodiment is 0.40% or less. The Si content is preferably 0.35% or less, or 0.30% or less.

[0020] (Mn: 1.00% or more, 2.20% or less) Mn is an element that enhances the hardenability of steel and improves its strength and wear resistance. From the viewpoint of ensuring strength and wear resistance, in this embodiment, the Mn content is 1.00% or more. Preferably, the Mn content is 1.10% or more, or 1.20% or more. On the other hand, if the Mn content exceeds 2.20%, the low-temperature toughness decreases. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the Mn content is 2.20% or less. Preferably, the Mn content is 2.00% or less.

[0021] (P:0.020% or less) P is an impurity element. P is also an element that degrades low-temperature toughness by segregating at grain boundaries. From the viewpoint of ensuring low-temperature toughness, the P content in this embodiment is 0.020% or less. Preferably, the P content is 0.019% or less, or 0.018% or less. The lower limit of the P content is not limited and may be 0%. From the viewpoint of manufacturing cost, the P content may be 0.001% or more.

[0022] (S:0.0060% or less) S is an impurity element. S also degrades low-temperature toughness by combining with Mn to form MnS. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the S content is 0.0060% or less. Preferably, the S content is 0.0040% or less, or 0.0020% or less. The lower limit of the S content is not limited and may be 0%. From the viewpoint of manufacturing cost, the S content may be 0.0001% or more.

[0023] (Al: 0.010% or more, 0.050% or less) Al is a deoxidizing element that suppresses the coarsening of γ grains by forming fine nitrides, thereby improving low-temperature toughness. From the viewpoint of ensuring deoxidizing effect and low-temperature toughness, the Al content is 0.010% or more. Preferably, the Al content is 0.020% or more. On the other hand, if the Al content exceeds 0.050%, the formation of coarse Al oxides and the increase in island-like martensites reduce wear resistance and low-temperature toughness. From the viewpoint of ensuring wear resistance and low-temperature toughness, in this embodiment, the Al content is 0.050% or less. Preferably, the Al content is 0.040% or less.

[0024] (Ti: 0.010% or more, 0.020% or less) Ti is an element that suppresses the coarsening of γ grains by forming fine nitrides, thereby improving low-temperature toughness. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the Ti content is 0.010% or more. Preferably, the Ti content is 0.011% or more, or 0.012% or more. On the other hand, if the Ti content exceeds 0.020%, coarse Ti carbonitrides will precipitate, and the wear resistance and low-temperature toughness will deteriorate. From the viewpoint of ensuring wear resistance and low-temperature toughness, in this embodiment, the Ti content is 0.020% or less. Preferably, the Ti content is 0.019% or less, or 0.018% or less.

[0025] (N: 0.0010% or more, 0.0060% or less) N is an impurity element that suppresses the coarsening of γ grains by forming fine nitrides, thereby improving low-temperature toughness. From the viewpoint of ensuring low-temperature toughness, the N content is 0.0010% or more. Preferably, the N content is 0.0015% or more, and more preferably 0.0020% or more. On the other hand, if the N content exceeds 0.0060%, the low-temperature toughness deteriorates due to the formation of coarse nitrides. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the N content is 0.0060% or less. Preferably, the N content is 0.0055% or less, or 0.0050% or less.

[0026] (B: 0.0005% or more, 0.0020% or less) B is an element that improves the hardenability of steel and enhances its strength and wear resistance. From the viewpoint of ensuring strength and wear resistance, in this embodiment, the B content is 0.0005% or more. Preferably, the B content is 0.0007% or more, or 0.0008% or more. On the other hand, B deteriorates the surface quality of steel billets produced by continuous casting by precipitation and reduces low-temperature toughness. From the viewpoint of ensuring the surface quality of steel billets and ensuring low-temperature toughness, in this embodiment, the B content is 0.0020% or less. Preferably, the B content is 0.0018% or less, or 0.0016% or less.

[0027] (O: 0.004% or less) O is an impurity element and also degrades low-temperature toughness by forming coarse oxides. From the viewpoint of ensuring low-temperature toughness, the O content in this embodiment is 0.004% or less. Preferably, the O content is 0.0035% or less, or 0.003% or less. The lower limit of the O content is not limited and may be 0%, but from the viewpoint of manufacturing cost, the O content may be 0.0005% or more.

[0028] The remainder of the chemical composition of the high-tensile steel sheet according to this embodiment consists of iron (Fe) and impurities. Impurities are components that are mixed in during the industrial manufacturing of steel materials due to raw materials such as ore and scrap, or other factors.

[0029] The high-tensile steel sheet according to this embodiment may further contain, if necessary, one or more of the following select elements Nb, Cu, Ni, Cr, Mo, V, Mg, Ca, and rare earth elements (REM) in place of a portion of Fe.

[0030] (Nb: 0% or more, 0.030% or less) Nb exhibits a strong γ-recrystallization suppression effect in TMCP (Thermo-Mechanical Control Process), improving low-temperature toughness. In this embodiment, the lower limit of the Nb content is not limited and may be 0%. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the Nb content may be 0.001% or more. On the other hand, if the Nb content exceeds 0.030%, coarse Nb carbonitrides precipitate, degrading wear resistance and low-temperature toughness. From the viewpoint of ensuring wear resistance and low-temperature toughness, in this embodiment, the Nb content is 0.030% or less. Preferably, the Nb content is 0.029% or less, or 0.028% or less.

[0031] (Cu: 0% or more, 0.50% or less) Cu is an element that improves the hardenability of steel and enhances its strength and wear resistance. In this embodiment, the lower limit of the Cu content is not limited and may be 0%. From the viewpoint of ensuring strength and wear resistance, in this embodiment, the Cu content may be 0.01% or more. However, if the Cu content exceeds 0.50%, it reduces low-temperature toughness as coarse Cu precipitates form. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the Cu content is 0.50% or less. Preferably, the Cu content is 0.45% or less, or 0.40% or less.

[0032] (Ni: 0% or more, 0.50% or less) Ni is an element that improves the hardenability of steel, enhances its strength and wear resistance, and also improves its low-temperature toughness. In this embodiment, the lower limit of the Ni content is not limited and may be 0%. From the viewpoint of ensuring strength, wear resistance, and low-temperature toughness, the Ni content may be 0.01% or more in this embodiment. On the other hand, Ni is an expensive element, and including it in excess would lead to increased manufacturing costs, which is undesirable. From the viewpoint of suppressing manufacturing costs, the Ni content in this embodiment is 0.50% or less. Preferably, the Ni content is 0.45% or less, or 0.40% or less.

[0033] (Cr: 0% or more, 0.50% or less) Cr is an element that improves the hardenability of steel and enhances its strength and wear resistance. In this embodiment, the lower limit of the Cr content is not limited and may be 0%. From the viewpoint of ensuring strength and wear resistance, in this embodiment, the Cr content may be 0.01% or more. On the other hand, if the Cr content exceeds 0.50%, coarse Cr carbides precipitate, reducing wear resistance and low-temperature toughness. From the viewpoint of ensuring wear resistance and low-temperature toughness, in this embodiment, the Cr content is 0.50% or less. Preferably, the Cr content is 0.45% or less, or 0.40% or less.

[0034] (Mo: 0% or more, 0.50% or less) Mo is an element that improves the hardenability of steel and enhances its strength and wear resistance. In this embodiment, the lower limit of the Mo content is not limited and may be 0%. From the viewpoint of ensuring strength and wear resistance, in this embodiment, the Mo content may be 0.01% or more. On the other hand, if the Mo content exceeds 0.50%, coarse Mo carbides precipitate, reducing wear resistance and low-temperature toughness. From the viewpoint of ensuring wear resistance and low-temperature toughness, in this embodiment, the Mo content is 0.50% or less. Preferably, the Mo content is 0.45% or less, or 0.40% or less.

[0035] (V: 0% or more, 0.10% or less) V is an element that forms carbides and nitrides, improving the strength and wear resistance of steel. In this embodiment, the lower limit of the V content is not limited and may be 0%. From the viewpoint of ensuring strength and wear resistance, in this embodiment, the V content may be 0.01% or more. On the other hand, if the V content exceeds 0.10%, coarse V carbonitrides precipitate, reducing wear resistance and low-temperature toughness. From the viewpoint of ensuring wear resistance and low-temperature toughness, in this embodiment, the V content is 0.10% or less. Preferably, the V content is 0.08% or less, or 0.06% or less.

[0036] (Mg: 0% or more, 0.0050% or less) Mg is an element that forms oxides, sulfides, and oxysulfides, suppressing the formation of coarse inclusions and improving low-temperature toughness. In this embodiment, the lower limit of the Mg content is not limited and may be 0%. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the Mg content may be 0.0010% or more. On the other hand, if the Mg content exceeds 0.0050%, coarse Mg inclusions precipitate, reducing wear resistance and low-temperature toughness. From the viewpoint of ensuring wear resistance and low-temperature toughness, the Mg content is 0.0050% or less. Preferably, the Mg content is 0.0040% or less, or 0.0030% or less.

[0037] (Ca: 0% or more, 0.0050% or less) Ca is an element that forms oxides, sulfides, and oxysulfides, suppressing the formation of coarse inclusions and improving low-temperature toughness. In this embodiment, the lower limit of the Ca content is not limited and may be 0%. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the Ca content may be 0.0010% or more. On the other hand, if the Ca content exceeds 0.0050%, coarse Ca inclusions precipitate, reducing wear resistance and low-temperature toughness. From the viewpoint of ensuring wear resistance and low-temperature toughness, the Ca content is 0.0050% or less. Preferably, the Ca content is 0.0040% or less, or 0.0030% or less.

[0038] (Rare earth elements (REM): 0% or more, 0.0200% or less) Rare earth elements (REM) refer to the 17 elements in total, consisting of the two elements Sc and Y, and the 15 lanthanide elements such as La, Pr, and Nd. The REM content refers to the total content of these 17 elements. The lower limit of the REM content is not limited and may be 0%. Like Mg and Ca, REM is an element that suppresses the formation of coarse inclusions by forming oxides, sulfides, and oxysulfides, thereby improving low-temperature toughness. From the viewpoint of ensuring low-temperature toughness, the REM content in this embodiment may be 0.0010% or more. On the other hand, if the REM content exceeds 0.0200%, coarse REM inclusions will precipitate, reducing wear resistance and low-temperature toughness. From the viewpoint of ensuring wear resistance and low-temperature toughness, the REM content is 0.0200% or less. Preferably, the REM content is 0.0150% or less, or 0.0100% or less.

[0039] The high-tensile steel sheet according to this embodiment may further contain, if necessary, one or more of the following selected elements W, Co, Zr, Hf, Te, As, Sr, Sn, Sb, Bi, Ta, Zn, Pb, and Se in place of a portion of Fe.

[0040] (W: 0% or more, 0.100% or less) W is an element that improves the hardenability of steel and enhances its strength and wear resistance. In this embodiment, the lower limit of the W content is not limited and may be 0%. From the viewpoint of ensuring strength and wear resistance, in this embodiment, the W content may be 0.010% or more. On the other hand, if the W content exceeds 0.100%, coarse W carbides precipitate, reducing wear resistance and low-temperature toughness. From the viewpoint of ensuring wear resistance and low-temperature toughness, in this embodiment, the W content is 0.100% or less.

[0041] (Co: 0% or more, 0.100% or less) Co is an impurity element, but it also improves the hardenability of steel and enhances its strength and wear resistance. In this embodiment, the lower limit of the Co content is not limited and may be 0%. From the viewpoint of ensuring strength and wear resistance, in this embodiment, the Co content may be 0.010% or more. On the other hand, if the Co content exceeds 0.100%, coarse Co carbides precipitate, reducing wear resistance and low-temperature toughness. From the viewpoint of ensuring wear resistance and low-temperature toughness, in this embodiment, the Co content is 0.100% or less.

[0042] (Zr: 0% or more, 0.050% or less) Zr is an impurity element that forms oxides, sulfides, and oxysulfides, suppressing the formation of coarse inclusions and improving low-temperature toughness. In this embodiment, the lower limit of the Zr content is not limited and may be 0%. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the Zr content may be 0.001% or more. On the other hand, if the Zr content exceeds 0.050%, coarse Zr inclusions precipitate, reducing wear resistance and low-temperature toughness. From the viewpoint of ensuring wear resistance and low-temperature toughness, in this embodiment, the Zr content is 0.050% or less. Preferably, the Zr content is 0.030% or less, or 0.010% or less.

[0043] (Hf: 0% or more, 0.020% or less) Hf is an impurity element that forms oxides, sulfides, and oxysulfides, suppressing the formation of coarse inclusions and improving low-temperature toughness. In this embodiment, the lower limit of the Hf content is not limited and may be 0%. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the Hf content may be 0.001% or more. On the other hand, if the Hf content exceeds 0.020%, coarse Hf inclusions precipitate, reducing wear resistance and low-temperature toughness. From the viewpoint of ensuring wear resistance and low-temperature toughness, in this embodiment, the Hf content is 0.020% or less. The Hf content is preferably 0.010% or less, or 0.005% or less.

[0044] (Te: 0% or more, 0.050% or less) Te is an impurity element that forms oxides, sulfides, and oxysulfides, suppressing the formation of coarse inclusions and improving low-temperature toughness. In this embodiment, the lower limit of the Te content is not limited and may be 0%. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the Te content may be 0.001% or more. On the other hand, if the Te content exceeds 0.050%, coarse Te inclusions precipitate, reducing wear resistance and low-temperature toughness. From the viewpoint of ensuring wear resistance and low-temperature toughness, in this embodiment, the Te content is 0.050% or less. Preferably, the Te content is 0.030% or less, or 0.010% or less.

[0045] (As: 0% or more, 0.050% or less) As is an impurity element and also an element that reduces the hot workability of steel. From the viewpoint of ensuring hot workability, in this embodiment, the As content is 0.050% or less. Preferably, the As content is 0.020% or less, or 0.010% or less. In this embodiment, the lower limit of the As content is not limited and may be 0%. From the viewpoint of manufacturing cost, the As content may be 0.0001% or more.

[0046] (Sr: 0% or more, 0.020% or less) Sr is an impurity element that forms oxides, sulfides, and oxysulfides, suppressing the formation of coarse inclusions and improving low-temperature toughness. In this embodiment, the lower limit of the Sr content is not limited and may be 0%. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the Sr content may be 0.001% or more. On the other hand, if the Sr content exceeds 0.020%, coarse Sr inclusions precipitate, reducing wear resistance and low-temperature toughness. From the viewpoint of ensuring wear resistance and low-temperature toughness, in this embodiment, the Sr content is 0.020% or less. Preferably, the Sr content is 0.010% or less, or 0.005% or less.

[0047] (Sn: 0% or more, 0.100% or less) Sn is an impurity element, but it is also an element that enhances the corrosion resistance of steel. In this embodiment, the lower limit of the Sn content is not limited and may be 0%. From the viewpoint of improving corrosion resistance, in this embodiment, the Sn content may be 0.001% or more. On the other hand, if the Sn content exceeds 0.100%, the low-temperature toughness decreases. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the Sn content is 0.100% or less. The Sn content is preferably 0.050% or less, or 0.020% or less.

[0048] (Sb: 0% or more, 0.050% or less) Sb is an impurity element, but it is also an element that enhances the corrosion resistance of steel. In this embodiment, the lower limit of the Sb content is not limited and may be 0%. From the viewpoint of improving corrosion resistance, in this embodiment, the Sb content may be 0.001% or more. On the other hand, if the Sb content exceeds 0.050%, the low-temperature toughness decreases. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the Sb content is 0.050% or less. Preferably, the Sb content is 0.030% or less, or 0.010% or less.

[0049] (Bi: 0% or more, 0.100% or less) Bi is an impurity element and also an element that reduces the hot workability of steel. From the viewpoint of ensuring hot workability, in this embodiment, the Bi content is 0.100% or less. Preferably, the Bi content is 0.050% or less, or 0.020% or less. In this embodiment, the lower limit of the Bi content is not limited and may be 0%. From the viewpoint of manufacturing cost, the Bi content may be 0.0001% or more.

[0050] (Ta: 0% or more, 0.100% or less) Ta is an impurity element that forms oxides, sulfides, and oxysulfides, suppressing the formation of coarse inclusions and improving low-temperature toughness. In this embodiment, the lower limit of the Ta content is not limited and may be 0%. From the viewpoint of improving low-temperature toughness, in this embodiment, the Ta content may be 0.001% or more. On the other hand, if the Ta content exceeds 0.100%, coarse Ta inclusions precipitate, reducing wear resistance and low-temperature toughness. From the viewpoint of ensuring wear resistance and low-temperature toughness, in this embodiment, the Ta content is 0.100% or less. Preferably, the Ta content is 0.050% or less, or 0.020% or less.

[0051] (Zn: 0% or more, 0.020% or less) Zn is an impurity element, but it is also an element that enhances the corrosion resistance of steel. In this embodiment, the lower limit of the Zn content is not limited and may be 0%. From the viewpoint of improving corrosion resistance, in this embodiment, the Zn content may be 0.001% or more. On the other hand, if the Zn content exceeds 0.020%, the low-temperature toughness decreases. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the Zn content is 0.020% or less. The Zn content is preferably 0.010% or less, or 0.005% or less.

[0052] (Pb: 0% or more, 0.090% or less) Pb is an impurity element and also an element that reduces the hot workability of steel. From the viewpoint of ensuring hot workability, in this embodiment, the Pb content is 0.090% or less. Preferably, the Pb content is 0.050% or less, or 0.020% or less. In this embodiment, the lower limit of the Pb content is not limited and may be 0%. From the viewpoint of manufacturing cost, the Pb content may be 0.0001% or more.

[0053] (Se: 0% or more, 0.020% or less) Se is an impurity element. Se is also an element that degrades low-temperature toughness by combining with Mn to form MnSe. From the viewpoint of ensuring low-temperature toughness, in this embodiment, the Se content is 0.020% or less. Preferably, the Se content is 0.010% or less, or 0.005% or less. The lower limit of the Se content is not limited and may be 0%. From the viewpoint of manufacturing cost, the Se content may be 0.0001% or more.

[0054] Next, the microstructure of the high-tensile steel sheet according to this embodiment will be described. The microstructure of the high-tensile steel sheet in this embodiment, located at a depth of 0.7 mm from the surface in the thickness direction, may include ferrite, pearlite, upper bainite, lower bainite, and martensite.

[0055] (10,000 μm 2 (Number of cementite particles with a major axis of 400 nm or more included in the region) Coarse cementite particles become the starting point for the generation of microcracks during wear and brittle fracture. Therefore, refining the cementite is effective in obtaining good wear resistance and low-temperature toughness. In the case of steel sheets having the chemical composition of this embodiment as described above, the cementite particle size is typically 10,000 μm. 2 In a region (100 μm × 100 μm square), there are approximately 10,000 to 100,000 cementite particles, but if the cementite particles have a major axis of less than 400 nm, the degree of stress concentration will be small. In other words, if the cementite particles are minute, the probability of them becoming the initiation point for microcracks during wear or brittle fracture is small, so controlling the number of coarse cementite particles with a major axis of 400 nm or more is particularly important for improving wear resistance and low-temperature toughness. In this embodiment, from the viewpoint of ensuring wear resistance and low-temperature toughness, 10,000 μm 2 The number of coarse cementite particles with a major axis of 400 nm or more included in the region is 5,000 or less. Preferably, it is 3,500 or less. Since a smaller number of coarse cementite particles is preferable, 10,000 μm 2The number of elements in this region may be zero, but in practical operation, it is difficult to achieve zero. There is no particular lower limit to the number of coarse cementite elements, but for example, it may be 1,000 or more.

[0056] In this embodiment, the number of cementite particles can be determined by the following method. A test specimen for cementite observation is prepared from a high-tensile steel sheet according to this embodiment. The test specimen is prepared so that the observation surface is perpendicular to the thickness direction (including the rolling direction and the width direction) at a depth of 0.7 mm from the surface of the high-tensile steel sheet in the thickness direction. After polishing the observation surface of the test specimen to a mirror finish, it is immersed in a Nital etching solution for about 10 seconds to reveal the microstructure by etching. The etched observation surface is observed using a scanning electron microscope (SEM) to obtain the Z-contrast image, also known as the COMPO image, from the backscattered electron detector. The observation magnification is 3,000x. Furthermore, the total observation field area is 10,000 μm² within the observation field described above. 2 Set the number of observation fields so that this is the case.

[0057] In each field of view, particles are identified based on contrast. Identifying particles based on contrast in each field of view is, of course, possible for anyone skilled in the art. The major axis of a particle can be determined by image analysis of the observed image in the COMPO image. Here, "major axis of a particle" refers to the longest distance between any two points on the contour of the particle. Using the image of the particles measured above, particles with a major axis of 400 nm or more are identified as "coarse particles" using the method described above.

[0058] Furthermore, point analysis is performed on the identified coarse particles (particles with a major axis of 400 nm or more) using energy dispersive X-ray spectroscopy (EDS). In the EDS point analysis, the acceleration voltage is set to 3-5 kV, and measurements are taken at any position within the coarse particles. Based on the EDS analysis results for each coarse particle, coarse particles containing 30% or more Fe and 15% or more C (atomic percent) are identified as cementite with a major axis of 400 nm or more. The sum of the numbers identified in each observation field using the above method is calculated as 10,000 μm 2 This is defined as the number of cementite particles with a major axis of 400 nm or more that are included in the region.

[0059] (Ferrite area ratio) The microstructure of the high-tensile steel sheet according to this embodiment is a mixed structure of ferrite, pearlite, upper bainite, lower bainite, and martensite. From the viewpoint of ensuring sufficient strength and wear resistance, it is preferable that the area ratio of ferrite, which is the soft phase, be low, preferably 5% or less. The area ratio of ferrite is more preferably 3% or less, and may be 0%.

[0060] In addition to ferrite, pearlite, upper bainite, lower bainite, and martensite, the microstructure of the high-tensile steel sheet according to this embodiment may also contain trace amounts of precipitates, inclusions, etc. However, in the microstructure of the high-tensile steel sheet according to this embodiment, the area ratio of precipitates, inclusions, etc. is negligibly small compared to ferrite, pearlite, upper bainite, lower bainite, and martensite.

[0061] In this embodiment, the area ratio of ferrite can be determined by the following method. A test specimen for microstructural observation is prepared from a high-tensile steel sheet according to this embodiment. The test specimen is prepared so that the observation surface is perpendicular to the thickness direction (including the rolling direction and the width direction) at a position 0.7 mm below the surface of the high-tensile steel sheet in the thickness direction. After electropolishing the observation surface of the test specimen, analysis is performed by electron backscatter diffraction (EBSD). The measurement magnification is 300x, and measurements are performed in a 300 μm × 300 μm area at a measurement pitch of 0.3 μm. The confidence index (CI) is set to 0.1 or higher. The determination of ferrite, pearlite, upper bainite, lower bainite, and martensite is performed by setting the threshold of KAM (Kernel Average Misorientation) with respect to the third nearest neighbor to 1.0. Regions where KAM is 1.0 or less are ferrite, and regions where KAM is greater than 1.0 are pearlite, upper bainite, lower bainite, or martensite. Therefore, the ferrite area ratio is determined by the ratio of measurement points with a KAM of 1.0 or less to the third nearest neighbor point, relative to all EBSD measurement points in the specified measurement area.

[0062] <Mechanical properties> The high-tensile steel plate according to this embodiment has excellent strength, wear resistance, and low-temperature toughness.

[0063] (Abrasion resistance) The high-tensile steel plate according to this embodiment has excellent wear resistance. Wear resistance is evaluated by a gouging wear test. After grinding the high-tensile steel plate to 0.7 mm below the surface, the abrasion test grinding wheel is applied to the ground surface, and a load is applied in the thickness direction of the plate for measurement. The abrasion test is conducted using an A36P grinding wheel, which has a brown alumina-based A abrasive material, a grit size of 36, and a hardness of P, with a load of 14.1 kgf, a rotation speed of 30 rpm, and an ambient temperature of 200°C. To avoid the influence of the surface condition of the test piece, the weight loss rate during the abrasion test is measured over a 5-minute period from 3 minutes to 8 minutes after the start of the test, and the weight loss rate is calculated from the time average. It is preferable that the weight loss rate of the high-tensile steel plate according to this embodiment is 0.12 g / min or less, or 0.10 g / min or less, when the above gouging wear test is performed.

[0064] (Tensile Strength, Yield Strength) The tensile strength and yield strength of the high-strength steel sheet according to the present embodiment can be obtained by the following method. A plate-shaped tensile test specimen is prepared from the thickness center of the high-strength steel sheet according to the present embodiment. In this process, the axial direction of the plate-shaped test specimen is perpendicular to the rolling direction. As the plate-shaped test specimen, JIS No. 14B specified in JIS Z 2241:2022 is used. A tensile test conforming to JIS Z 2241:2022 is performed on the tensile test specimen at room temperature in the atmosphere. Tensile strength TS (MPa) and yield strength YS (MPa) are obtained from the results of the tensile test. Note that yield strength YS is defined as 0.2% proof stress. It is preferable that the high-strength steel sheet according to the present embodiment has a tensile strength of 780 MPa to 930 MPa and a yield strength of 685 MPa or more.

[0065] (Low-temperature Toughness) The low-temperature toughness of the high-strength steel sheet according to the present embodiment is represented by Charpy impact absorption energy at -20°C. The Charpy impact absorption energy is measured in accordance with the provisions of JIS Z 2242:2023 by a Charpy impact test at -20°C using an impact blade with a radius of 2 mm. The Charpy impact absorption energy is measured using three test specimens, and calculated by averaging the measurement results thereof. For the test, a V-notched test specimen is used, which is sampled from the thickness center portion of the high-strength steel sheet with its longitudinal direction parallel to the rolling direction, and has a notch engraved in the direction in which a crack propagates in the width direction. The thickness t of the test specimen s varies depending on the thickness t of the high-strength steel sheet. When 4.0 mm ≤ t ≤ 6.0 mm, t s is 2.5 mm; when 6.0 mm < t ≤ 11.0 mm, t s is 5.0 mm; when 11.0 mm < t, ts is 10.0 mm, and t sFor the absorbed energy of 2.5 mm and 5.0 mm test specimens, the obtained absorbed energy is evaluated after correcting it to the full-size absorbed energy by multiplying it by 4 and 2, respectively. The Charpy impact absorbed energy of three test specimens is measured at -20°C, and the average value of these measurements is taken as the Charpy impact absorbed energy of the high-tensile steel sheet of this embodiment at -20°C. From the viewpoint of ensuring low-temperature toughness, it is preferable that the Charpy impact absorbed energy of the high-tensile steel sheet of this embodiment at -20°C is 47 J or more, or 55 J or more.

[0066] <Shape of steel plate> The shape of the high-tensile steel sheet according to this embodiment is not particularly limited, but for example, the thickness of the high-tensile steel sheet is 4 to 16 mm. With a high-tensile steel sheet with a thickness of 4 to 16 mm, the number of coarse cementite particles can be stably reduced by the preferred manufacturing method described later, and excellent wear resistance and low-temperature toughness can be obtained.

[0067] <3. Manufacturing method for high-tensile steel sheets> Next, a preferred method for manufacturing the high-tensile steel sheet according to this embodiment will be described.

[0068] The method for manufacturing the high-tensile steel sheet according to this embodiment is not particularly limited, but for example, after melting steel satisfying the aforementioned chemical structure, steel billets may be produced by continuous casting. The steel billets are heated, hot-rolled, and then cooled by water cooling. The high-tensile steel sheet according to this embodiment may also be manufactured by winding it into a coil after hot rolling.

[0069] In the following, "Ar3" will be used as a symbol representing the temperature value of the transformation point in degrees Celsius, and when Ar3 has a unit, it will be written as Ar3(°C). The cast slab, which was cast using the above-mentioned chemical composition and molten steel treatment, is air-cooled to (Ar3-200)°C or below, and then reheated to a temperature range of 1000°C to 1300°C. "Ar3" is represented by the following formula (1). From the viewpoint of carbide solution formation, the reheating temperature is preferably 1050°C or higher. On the other hand, from the viewpoint of suppressing the coarsening of γ grains and improving low-temperature toughness, the reheating temperature is preferably 1250°C or lower.

[0070] Ar3=868-396×[C]+24.6×[Si]-68.1×[Mn] -20.7×[Cu]-36.1×[Ni]-24.8×[Cr] +29.1 × [Mo] ... Formula (1) Here, [C], [Si], [Mn], [Cu], [Ni], [Cr], and [Mo] represent the mass percentages of C, Si, Mn, Cu, Ni, Cr, and Mo, respectively.

[0071] After reheating, hot rolling is performed to refine the austenite structure. In hot rolling, an elongated γ-grain structure can be obtained by increasing the cumulative reduction ratio below 900°C. By maintaining the elongated γ-grain structure of the rolled steel sheet, the bainite and martensitic structures after transformation are refined, resulting in excellent low-temperature toughness. To obtain a sufficiently elongated γ-grain structure, the cumulative reduction ratio below 900°C may be 60% or more. If the cumulative reduction ratio below 900°C is less than 60%, the bainite and martensitic structures after transformation may not be sufficiently refined, potentially impairing low-temperature toughness. The cumulative reduction ratio below 900°C is preferably 70% or more.

[0072] In the hot rolling process according to this embodiment, it is preferable that the inter-pass time, which is the time from when the rolled steel sheet is gripped in the previous reduction pass until when it is gripped in the next reduction pass, is no more than 3 seconds in each rolling pass in the temperature range of 900°C or below. By keeping the inter-pass time to a maximum of 3 seconds in the temperature range of 900°C or below, a large amount of dislocations are introduced into the γ grains, and the cementite precipitated during cooling is refined. More preferably, the inter-pass time is 2 seconds or less. Under the above conditions, introducing a large number of dislocations into the austenite refines the cementite during cooling, improving wear resistance and low-temperature toughness.

[0073] The end temperature of hot rolling is preferably Ar3(°C) or higher, from the viewpoint of ending the hot rolling process in the temperature range where the microstructure of the high-tensile steel sheet is austenite. If the end temperature of hot rolling is below Ar3(°C), ferrite transformation may proceed before cooling begins, potentially impairing strength and wear resistance.

[0074] The high-tensile steel sheet according to this embodiment is subjected to accelerated cooling (primary cooling) after hot rolling. Accelerated cooling (primary cooling) is preferably started at a temperature of Ar3 (°C) or higher. The average cooling rate of accelerated cooling is preferably 10°C / s or higher. There is no particular upper limit to the average cooling rate of accelerated cooling, and it is naturally limited by the capacity of the water cooling system and the plate thickness.

[0075] Accelerated cooling (primary cooling) is preferably carried out until the surface temperature of the rolled steel sheet reaches 600°C or below, at which point cooling is stopped. If the primary cooling stop temperature is higher than 600°C, excessive ferrite precipitation may occur. The lower limit of the primary cooling stop temperature is preferably 300°C or higher, from the viewpoint of suppressing an excessive increase in strength and ensuring low-temperature toughness. After primary cooling is stopped, the rolled steel sheet is secondary cooled to room temperature at an average cooling rate of 0.10°C / s or less. The high-tensile steel sheet according to this embodiment is manufactured through the above process. [Examples]

[0076] Cast slabs were produced from molten steel having the chemical composition shown in Table 1. Note that blank spaces in Table 1 indicate that the content of each element is at an impurity level.

[0077] The manufactured slabs were subjected to a hot rolling process. First, each slab with a test number was reheated in a heating furnace at the reheating temperature shown in Table 2.

[0078] A hot rolling process was carried out on the reheated cast slabs. The cumulative reduction ratio and the maximum inter-pass time at temperatures below 900°C during the hot rolling process are shown in Table 2.

[0079] High-tensile steel sheets with the thicknesses listed in Table 2 were manufactured by performing primary and secondary cooling on hot-rolled steel sheets under the conditions described in Table 2.

[0080] [Evaluation Test] The following evaluation tests were performed on each high-tensile steel plate with the specified test number that was manufactured. (Test 1) Tensile test (Test 2) Microtissue observation test (Test 3) Cementite observation test (Test 4) Gouging wear test (Test 5) 2mm V-notch Charpy impact test

[0081] [(Test 1) Tensile Test] Tensile tests were conducted on the high-tensile steel plates of each test number using the method described above to determine the tensile strength TS (MPa) and yield strength YS (MPa). The obtained tensile strength TS (MPa) and yield strength (MPa) for each test number are shown in Table 3.

[0082] [(Test 2) Microtissue observation test] Microstructural observation tests were conducted on high-tensile steel plates for each test number. Test specimens were prepared using the method described above, and EBSD analysis was performed. Ferrite was identified from KAM, and its area percentage was determined. The area percentage (%) of ferrite for each test number is shown in Table 3.

[0083] [(Test 3) Cementite Observation Test] The cementite observation test was performed on the high-tensile steel plates of each test number using the method described above. After preparing the test specimens using the method described above and performing SEM analysis and EDS analysis, the cementite was measured by image analysis at 10,000 μm. 2 The number of cementite particles with a major axis of 400 nm or more within the specified region was measured. The number of cementite particles obtained for each test number is shown in Table 3.

[0084] [(Test 4) Gouging Abrasion Test] A gouging abrasion test was performed on the high-tensile steel plates of each test number using the method described above. Test specimens were prepared using the method described above, and the gouging abrasion test was performed to measure the weight loss rate. The weight loss rates obtained for each test number are shown in Table 3.

[0085] [(Test 5) 2mm V-notch Charpy impact test] A 2mm V-notch Charpy impact test was performed on the high-tensile steel plates of each test number using the method described above. Test specimens were prepared using the method described above, and the 2mm V-notch Charpy impact test was performed at -20°C to measure the absorbed energy. The absorbed energy values ​​for each test number were converted to full-size values ​​according to the plate thickness of the test specimen, as described above, and are shown in Table 3.

[0086] [Evaluation Results] As shown in Tables 1-3, the high-tensile steel sheets for test numbers 1-17 have chemical compositions within the range of the present invention and are 10,000 μm thick. 2 The number of cementite particles with a major axis of 400 nm or more in the region was reduced to 5,000 or less. As a result, the weight loss rate in the gouging abrasion test was 0.12 g / min or less, and the absorbed energy KV2 in the Charpy impact test was 47 J or more, demonstrating excellent abrasion resistance and low-temperature toughness.

[0087] The high-tensile steel sheets tested in tests 1 to 14 also exhibited favorable manufacturing methods, resulting in desirable tensile strength (TS), yield strength (YS), and ferrite area ratio. As a result, they demonstrated even better wear resistance and low-temperature toughness, with a weight loss rate of 0.10 g / min or less in the gouging abrasion test and an absorbed energy KV2 of 55 J or more in the Charpy impact test.

[0088] On the other hand, the high-tensile steel plate in test number 18 had too little cumulative reduction at temperatures below 900°C. As a result, the number of cementite particles was excessive, leading to insufficient wear resistance and low-temperature toughness.

[0089] In test number 19, the inter-pass time in the rolling pass below 900°C was too long. As a result, the number of cementite particles was excessive, leading to insufficient wear resistance and low-temperature toughness.

[0090] The high-tensile steel plate in test number 20 underwent an excessively fast secondary cooling rate. As a result, the number of cementite particles became excessive, leading to insufficient wear resistance and low-temperature toughness.

[0091] The high-tensile steel plate in test number 21 had too low a carbon content. As a result, it lacked sufficient strength and abrasion resistance.

[0092] The high-tensile steel plate in test number 22 had too high a carbon content. As a result, it had excessive strength and insufficient low-temperature toughness.

[0093] The high-tensile steel plate in test number 23 had too high a Si content. As a result, it lacked wear resistance and low-temperature toughness.

[0094] The high-tensile steel plate in test number 24 had too low a manganese content. As a result, the ferrite fraction was excessive, leading to insufficient wear resistance.

[0095] The high-tensile steel sheet in test number 25 had too high a manganese content. As a result, it lacked low-temperature toughness.

[0096] The high-tensile steel plate in test number 26 had too high an aluminum content. As a result, it lacked sufficient wear resistance and low-temperature toughness.

[0097] The high-tensile steel plate in test number 27 had too high a Ti content. As a result, it lacked wear resistance and low-temperature toughness.

[0098] The high-tensile steel plate in test number 28 had too high a Nb content. As a result, it lacked wear resistance and low-temperature toughness.

[0099] The high-tensile steel sheet in test number 29 had too high a copper content. As a result, it lacked sufficient low-temperature toughness.

[0100] The high-tensile steel plate in test number 30 had too high a chromium content. As a result, the number of cementite particles was excessive, leading to insufficient wear resistance and low-temperature toughness.

[0101] The high-tensile steel plate in test number 31 had too high a molybdenum content. As a result, it lacked wear resistance and low-temperature toughness.

[0102] The high-tensile steel plate in test number 32 had too high aluminium content. As a result, it lacked wear resistance and low-temperature toughness.

[0103] [Table 1A]

[0104] [Table 1B]

[0105] [Table 2]

[0106] [Table 3] [Industrial applicability]

[0107] According to this disclosure, it is possible to provide a non-heat-treated high-tensile steel sheet that has excellent wear resistance and low-temperature toughness without heat treatment such as tempering. For this reason, the high-tensile steel sheet of this disclosure is suitable as a welded structural steel material for construction machinery, industrial machinery, etc.

Claims

1. The chemical composition is expressed in mass percent. C: 0.110% or more, 0.210% or less, Si: 0.10% or more, 0.40% or less, Mn: 1.00% or more, 2.20% or less, P: 0.020% or less, S: 0.0060% or less, Al: 0.010% or more, 0.050% or less, Ti: 0.010% or more, 0.020% or less, N: 0.0010% or more, 0.0060% or less, B: 0.0005% or more, 0.0020% or less, and O: 0.004% or less It contains, with the remainder consisting of Fe and impurities. A high-tensile steel sheet in which the number of cementite particles with a major axis of 400 nm or more within a 100 μm x 100 μm square area is 5,000 or less.

2. The aforementioned chemical composition is further expressed in mass%, Nb: 0.030% or less, Cu: 0.50% or less, Ni: 0.50% or less, Cr: 0.50% or less, Mo: 0.50% or less V: 0.10% or less, Mg: 0.0050% or less, Ca: 0.0050% or less, REM: 0.0200% or less, The high-tensile steel sheet according to claim 1, comprising one or more selected from the group consisting of the following.

3. The aforementioned chemical composition is further expressed in mass%, W: 0.100% or less, Co: 0.100% or less, Zr: 0.050% or less, Hf: 0.020% or less, Te: 0.050% or less, As: 0.050% or less, Sr: 0.020% or less, Sn: 0.100% or less, Sb: 0.050% or less, Bi: 0.100% or less, Ta: 0.100% or less, Zn: 0.020% or less, Pb: 0.090% or less, Se: 0.020% or less, The high-tensile steel sheet according to claim 1 or 2, comprising one or more selected from the group consisting of the following.

4. The high-tensile steel plate according to claim 1 or 2, wherein the rate of weight loss when subjected to a gouging abrasion test under the conditions of a rotational speed of 30 rpm, a load of 14.1 kgf, and an ambient temperature of 200°C is 0.12 g / min or less.

5. The high-tensile steel plate according to claim 3, wherein the weight loss rate when subjected to a gouging abrasion test under the conditions of a rotational speed of 30 rpm, a load of 14.1 kgf, and an ambient temperature of 200°C is 0.12 g / min or less.

Citation Information

Patent Citations

  • Recording electrode

    JP1985006477A

  • Steel plate for LPG storage tank and its manufacturing method

    JP6582590B2